Dinamika Pemanfaatan Ruang dan Konflik Tenurial di Kawasan Konservasi Pulau Moyo, Nusa Tenggara Barat - Markum; Rosiady H. Sayuti; Sitti Hilyana; Galang Anugrah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Much has been studied about the agrarian issues and its conflicts in Indonesia, but few of them have been explored in the context of small islands designated as a conservation areas. To fill the gap, this paper aims to analyze the dynamics of spatial utilization and tenurial conflict in the conservation area of Moyo Island, West Nusa Tenggara. Based on qualitative methods, the data was gathered through observation, in-depth interviews with 20 key informants, and secondary sources. This study reveals that spatial utilization practices on Moyo Island are problematic which has triggered a conflict as consequence. Forest areas have been openly and collectively encroached on by the local community to become agricultural land due to a lack of control by the local government as the authority. Meanwhile, extensive fishing practices and tourism activities are threatening the long-term viability of coral reefs in coastal areas. These difficulties are also intertwined with tenurial conflicts between local communities and Nature Conservation Agency of West Nusa Tenggara regarding land boundaries as well as the problem among local people and the private sector purchasing and selling property under the table. All in all, this study offers policy recommendations to resolve those problems on conservation area of Moyo Island.